Blood pressure distribution in responders and initial non-responders in a population screening study. Issue 4 (December 1982) - Silman, A J; Locke, C M
Abstract : The distribution of diastolic blood pressure (DBP) was compared between those who responded to a first written request to attend at their general practitioner's surgery for screening for hypertension and those who need more intensive effort encouraging them to attend. After excluding 25% of the population whose current address could not be traced, 92% of the remainder were eventually seen and screened. There was no association between diastolic blood pressure and effort needed to bring the patient to screening, and this applied to all patients both with and without a history of hypertension. Thus it appears that unlike screening for cervical cancer, screening for hypertension may not selectively tend to miss the groups most at risk.